Anomalies in Net Present Value, Returns and Polynomials, and Regret Theory in Decision-Making - Nwogugu, Michael C. I.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book explores why Internal Rate of Return (IRR) and Net Present Value (NPV) are not necessarily accurate or efficient tools for valuation and decision-making. The author specifically addresses the discounting biases and framing effects inherent in the NPV/MIRR/IRR model and in related approaches such as Adjusted Present Value (APV), Net Future Value (NFV) and by extension, Polynomials. In doing so, the book presents a new way of solving higher order polynomials using invariants and homomorphisms and explains why the "Fundamental Theorem of Algebra", the Binomial Theorem and the "Descartes Sign Rule" are unreliable. Chapters also discuss how Intertemporal Asset Pricing Theory (IAPT) and Intertemporal Capital Asset Pricing Models (ICAPM) can produce inaccurate results in some circumstances. The conditions under which ICAPM and IAPT may be accurate are described; as well as why those conditions cannot, or are unlikely to exist. The conditions under which negative interest rates may exist or are justified are also outlined. Moreover, the author explains why traditional Consumption-Savings-Investment-Production models of allocation can be inefficient, and then introduces a new model of allocation that can be applied to individuals, households and companies. Finally, the book explains why the Elasticity of Intertemporal Substitution is a flawed concept and introduces the Marginal Rate of Intertemporal Joint Substitution. .
Chapter 1) Introduction -- Chapter 2) Spatio-Temporal Framing Anomalies in the NPV-MIRR-IRR Model and Related Approached, and Regret Theory -- Chapter 3) Regret Theory and Asset Pricing Anomalies in Incomplete Markets with Dynamic Un-aggregate Preferences -- Chapter 4) The Descartes Sign Rule and The Fourier-Budan Theorem are Wrong -- Chapter 5) MN-2 Invariants and Homomorphisms for Solving Polynomials; and Anomalies in The Binomial Theorem And The "Fundamental Theorem Of Algebra -- Chapter 6) The Historical And Current Concepts Of "Plain" Interest Rates and Forward Rates are, or Can Be, Misleading -- Chapter 7) On Algebraic Anomalies in Polynomials and Net Present Value Decisions -- Chapter 8) Some Biases And Evolutionary Homomorphisms Implicit in The Calculation Of Returns -- Chapter 9) Conclusion -- Chapter 10) References.
Keywords: Investment banking; Securities; Corporations-Finance.; Business enterprises-Finance.; Engineering mathematics; Quantitative Finance; Mathematical and Computational Engineering